Characterization of arbuscular mycorrhizal fungus communities of aquilaria crassna and tectona grandis roots and soils in thailand plantations - Chaiyasen,A. (Public Library of Science, 2015)
© 2014 Chaiyasen et al. Aquilaria crassna Pierre ex Lec. and Tectona grandis Linn.f. are sources of resin-suffused agarwood and teak timber, respectively. This study investigated arbuscular mycorrhizal (AM) fungus community structure in roots and rhizosphere soils of A. crassna and T. grandis from plantations in Thailand to understand whether AM fungal communities present in roots and rhizosphere soils vary with host plant species and study sites. Terminal restriction fragment length polymorphism complemented with clone libraries revealed that AM fungal community composition in A. crassna and T. grandis were similar. A total of 38 distinct terminal restriction fragments (TRFs) were found, 31 of which were shared between A. crassna and T. grandis. AM fungal communities in T. grandis samples from different sites were similar, as were those in A. crassna. The estimated average minimum numbers of AM fungal taxa per sample in roots and soils of T. grandis were at least 1.89 vs. 2.55, respectively, and those of A. crassna were 2.85 vs. 2.33 respectively. The TRFs were attributed to Claroideoglomeraceae, Diversisporaceae, Gigasporaceae and Glomeraceae. The Glomeraceae were found to be common in all study sites. Specific AM taxa in roots and soils of T. grandis and A. crassna were not affected by host plant species and sample source (root vs. soil) but affected by collecting site. Future inoculum production and utilization efforts can be directed toward the identified symbiotic associates of these valuable tree species to enhance reforestation efforts. Copyright: